2017
DOI: 10.1186/s13550-017-0283-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of α-radioimmunotherapy with different activity levels of the 213Bi-labeled monoclonal antibody MX35 in an ovarian cancer model

Abstract: BackgroundThe aim of this study was to compare the therapeutic efficacy of two different activity levels of the 213Bi-labeled monoclonal antibody MX35 in an ovarian cancer model. Sixty female BALB/c (nu/nu) mice were inoculated intraperitoneally with human ovarian cancer cells (OVCAR-3). Two weeks later, 40 mice were injected intraperitoneal (i.p.) with 1 ml of 213Bi-MX35, 3 MBq/mL (n = 20), or 9 MBq/mL (n = 20). An additional 20 mice received unlabeled MX35. Incidence of tumors and ascites was investigated 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…These radiopharmaceuticals have shown therapeutic efficacy in cancer indications such as multiple myeloma, 46,47 leukemia, 48,49 non-Hodgkin's lymphoma, 50 and disseminated ovarian cancer. 51 In this study, the bifunctional chelator p-SCN-Bn-CHX-A″-DTPA was conjugated to 2Rs15d, which resulted in a reproducible mixture of conjugates with an average of one DTPA-chelators per sdAb. After radiolabeling, the resulting radio-conjugate proved to be stable in the final buffer at 25 and 37 °C.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These radiopharmaceuticals have shown therapeutic efficacy in cancer indications such as multiple myeloma, 46,47 leukemia, 48,49 non-Hodgkin's lymphoma, 50 and disseminated ovarian cancer. 51 In this study, the bifunctional chelator p-SCN-Bn-CHX-A″-DTPA was conjugated to 2Rs15d, which resulted in a reproducible mixture of conjugates with an average of one DTPA-chelators per sdAb. After radiolabeling, the resulting radio-conjugate proved to be stable in the final buffer at 25 and 37 °C.…”
Section: ■ Discussionmentioning
confidence: 98%
“…Until now, most preclinical and clinical studies reported make use of mAbs and peptides as targeting vehicles in combination with 213 Bi. These radiopharmaceuticals have shown therapeutic efficacy in cancer indications such as multiple myeloma, , leukemia, , non-Hodgkin’s lymphoma, and disseminated ovarian cancer …”
Section: Discussionmentioning
confidence: 99%
“…When proposing use of an internal α‐emitter for cancer treatment, it is important to choose a radionuclide with physical properties apt for the application. Intraperitoneal therapy with α‐emitters has shown significant potential in murine models previously, mainly with short‐lived nuclides coupled to monoclonal antibodies . With longer lived nuclides, an unfavorable biodistribution in mice without tumors was found after IP injection of 227 Th coupled to trastuzumab .…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer [101] Bi-DTPA-PAN-622-mAb A pilot therapy study with 213 Bi-DTPA-PAN-622 demonstrated a significant effect on the primary tumor.…”
Section: Bi-mx35-mabmentioning
confidence: 99%